Thermal conductor and method for producing same
The thermal conductor integrates a high thermal conductivity material within a porous fiber-reinforced resin structure, addressing the challenge of achieving both light weight and rigidity while maintaining effective heat dissipation.
Patent Information
- Application Number
- JP2020564283
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-29
- Filing Date
- 2020-11-11
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-11-11
AI Technical Summary
Existing thermal conductors face challenges in achieving both excellent light weight and rigidity while maintaining effective heat dissipation properties, as they often rely on dense materials that compromise on weight or rigidity.
A thermal conductor comprising a sheet-like thermal conductivity material with an in-plane thermal conductivity of 300 W/m·K or more, integrated within a porous structure made of reinforced fibers and resin, which covers at least two end faces and both sides of the thermal conductive material to enhance rigidity and heat dissipation.
The proposed thermal conductor achieves a balance of excellent light weight, rigidity, and heat dissipation properties, making it suitable for various industrial applications, including electronic devices and automotive components.
Smart Images

Figure 0007661699000002 
Figure 0007661699000003 
Figure 0007661699000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermal conductor, a case using the thermal conductor, and a method for manufacturing the thermal conductor. [Background technology]
[0002] In recent years, market demand for light weight has been increasing year by year for industrial products such as automobiles, aircraft, and electronic devices. In addition, with the improvement in performance of heat generating modules such as engines, motors, and processors, market demand for heat dissipation has also been increasing year by year. In order to meet such demands, molded products having excellent light weight and high thermal conductivity are widely used for various industrial applications. In particular, thermal conductors that combine a thermal conductive material having high thermal conductivity with a lightweight material having excellent light weight have excellent heat dissipation properties in addition to excellent light weight, and are expected to be used in various products and are being widely studied.
[0003] Patent Document 1 describes an invention of a thermal conductor in which a thermally conductive material and a rigidity retention material made of fiber-reinforced plastic are laminated. It is said that by laminating a thermally conductive material and a rigidity retention material made of fiber-reinforced plastic, it is possible to obtain a thermal conductor that combines excellent thermal conductivity with excellent lightweight properties.
[0004] Patent Document 2 describes an invention of a thermal conductor in which a laminate of graphite sheets is covered with a resin layer. It is said that by forming a case from graphite sheets and resin, it is possible to achieve both excellent thermal conductivity and excellent light weight.
[0005] Patent Document 3 describes an invention of a thermal conductor in which a graphite sheet is sandwiched between two sponge layers. It is said that excellent thermal conductivity can be obtained by sandwiching the graphite sheet between the two sponge layers. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2016 / 002457 [Patent Document 2] JP 2006-95935 A [Patent Document 3] International Publication No. 2018 / 198293 Summary of the Invention [Problem to be solved by the invention]
[0007] The thermal conductor in Patent Document 1 is said to be able to achieve both excellent thermal conductivity and excellent light weight by laminating a thermal conductive material and a rigidity retaining material, but the rigidity retaining material is a dense fiber-reinforced plastic, and there is room for improvement in terms of light weight.
[0008] The thermal conductor in Patent Document 2 is said to be able to achieve both excellent thermal conductivity and excellent light weight by coating the surface and ends of the graphite sheet with resin, but the resin coating the graphite sheet is dense and there is room for improvement in the light weight. In addition, since the coating is made of unreinforced resin, the rigidity of the thermal conductor is thought to be low.
[0009] The thermal conductor in Patent Document 3 is said to have excellent thermal conductivity by sandwiching a graphite sheet between two sponge layers. The sponge layers are foamed resin, and although they are lightweight, they are thought to have very low rigidity.
[0010] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a thermal conductor that combines excellent light weight and excellent rigidity and has excellent heat dissipation properties. [Means for solving the problem]
[0011] In order to solve the above problems, the thermal conductor of the present invention has the following configuration.
[0012] A thermal conductor comprising a sheet-shaped thermally conductive material (II) having an in-plane thermal conductivity of 300 W / m·K or more contained in a porous structure (I) made of reinforcing fibers and resin. Effect of the Invention
[0013] According to the present invention, it is possible to obtain a thermal conductor which is excellent in both light weight and rigidity and has excellent heat dissipation properties. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a thermal conductor of the present invention; [Diagram 2] FIG. 1 is a schematic diagram showing another embodiment of a thermal conductor of the present invention; [Diagram 3] FIG. 1 is a schematic diagram showing an embodiment of a thermal conductor that is excluded from the embodiments of the present invention. [Figure 4] Schematic diagram showing heat dissipation evaluation DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] <Thermal conductor> The porous structure (I) constituting the thermal conductor of the present invention contains a sheet-shaped thermally conductive material (II) (hereinafter, may be simply referred to as thermally conductive material (II)). The term "containing" as used herein means that the thermally conductive material (II) is present as a part of the layer of the porous structure (I).
[0017] For example, as shown in FIG. 1, the porous structure (I) 2 covers one end face (the end face on the right side in FIG. 1) and one surface (the upper surface in FIG. 1) of the thermally conductive material (II) 3, and as shown in FIG. 2, the porous structure (I) 2 covers both sides (both surfaces) and all end faces of the thermally conductive material (II) 3, that is, the porous structure (I) contains the thermally conductive material (II). On the other hand, as shown in FIG. 3, the porous structure (I) contains the thermally conductive material (II) in an embodiment in which all end faces of the thermally conductive material (II) 3 are exposed, that is, the thermally conductive material (II) alone is considered to form an independent layer. This embodiment in which the thermally conductive material (II) is contained in the porous structure (I) bears the stress applied to the thermal conductor, suppressing the transfer of stress to the thermally conductive material (II), and suppressing the destruction of the thermally conductive material (II).
[0018] The porous structure (I) preferably covers at least two end faces of the thermally conductive material (II), more preferably covers both sides of the thermally conductive material (II), and even more preferably covers both sides and all of the end faces of the thermally conductive material (II), i.e., encapsulates the thermally conductive material (II).
[0019] In the present invention, the porous structure (I) may cover the heat conductive material (II) via another member such as an adhesive, a buffer material, etc. Also, there may be a gap between the porous structure (I) and the heat conductive material (II).
[0020] However, in the present invention, it is preferable that at least one end face of the heat conductive material (II) is in direct contact with the porous structure (I) without any other member. It is also preferable that at least one surface of the heat conductive material (II) is in contact with the porous structure (I). By directly contacting the heat conductive material (II) with the porous structure (I) in this way, the heat transferred from the surface of the heat conductor can be rapidly transferred from the porous structure (I) to the heat conductive material (II).
[0021] Furthermore, in the present invention, it is preferable that the thermally conductive material (II) is not bonded to the porous structure (I). In order to bond the thermally conductive material (II) and the porous structure (I), it is generally necessary to interpose an adhesive between them, but the proportion of the thermally conductive material (II) in the thermal conductor decreases due to the adhesive, and the heat dissipation property of the thermal conductor decreases. In addition, since the thermally conductive material (II) is not bonded to the porous structure (I), the proportion of the stress applied to the thermal conductor that is borne by the porous structure (I) increases, and therefore the transmission of stress to the thermally conductive material (II) is suppressed, and the destruction of the thermally conductive material (II) can be suppressed.
[0022] The thermal conductor of the present invention preferably has a flexural modulus of 3 GPa or more, more preferably 5 GPa or more. The upper limit of the flexural modulus of the thermal conductor is not particularly limited, but is usually about 20 GPa. By having a flexural modulus of 3 GPa or more, the thermal conductor becomes a rigid structure and can be suitably used for housings and the like. As a means for setting the flexural modulus within this range, for example, a method of using a porous structure made of a fiber-reinforced resin as the porous structure (I) can be mentioned.
[0023] The thermal conductor of the present invention preferably has a bending stiffness per unit width of 0.3 N·m or more, more preferably 0.5 N·m or more, and even more preferably 1.5 N·m or more. The higher the bending stiffness per unit width of the thermal conductor, the better, so there is no particular upper limit to the bending stiffness per unit width, but it is usually around 45 N·m. The bending stiffness per unit width is determined by the elastic modulus E (Pa) and second moment of area I (m 4 ) and the width b (m) of the thermal conductor, it can be calculated using the following formula. · Bending stiffness per unit width (N·m) = E (Pa) × I (m 4 ) / b(m) In addition, if the cross section of the thermal conductor is rectangular, the second moment of area I of the rectangular cross section is bh 3 / 12(m 4 ), it can be calculated using the following formula: · Bending stiffness per unit width (N·m) = E (Pa) × h3 (m 3 ) / 12 As a means for setting the bending stiffness per unit width within the above range, for example, a method of using a porous structure made of a fiber-reinforced resin as the porous structure (I) can be mentioned, and also a method of making the thickness of the thermal conductor thick can be mentioned.
[0024] The thermal conductor of the present invention preferably has a maximum thickness of 0.3 mm to 3.0 mm, more preferably 0.5 mm to 1.5 mm. Although reducing the thickness of the thermal conductor has the effect of reducing the weight, a thermal conductor thinner than 0.3 mm may lack rigidity.
[0025] The thermal conductor of the present invention preferably has a specific gravity of 1.00 or less, more preferably 0.80 or less, and even more preferably 0.50 or less. A thermal conductor with a lower specific gravity has excellent lightness, but a specific gravity of 0.10 or less may result in insufficient rigidity.
[0026] A part of the surface of the thermal conductor or the entire surface of the thermal conductor may be covered with a resin. By covering the thermal conductor with a resin, short circuits caused by exposure of the reinforcing fibers can be prevented. This is also preferable from the viewpoint of design and mechanical properties.
[0027] [Thermal Conductive Material (II)] In the present invention, the thermally conductive material (II) is in the form of a sheet, and its in-plane thermal conductivity is 300 W / m·K or more. The in-plane thermal conductivity of the thermally conductive material (II) is preferably 500 w / m·K or more, and more preferably 1000 w / m·K or more. The higher the in-plane thermal conductivity, the more preferable it is, so there is no particular limit to the upper limit of the in-plane thermal conductivity, but thermally conductive materials having an in-plane thermal conductivity of about 2000 W / m·K are known. If the in-plane thermal conductivity of the thermally conductive material (II) is 300 W / m·K or more, the thermal diffusion in the in-plane direction of the thermal conductor is excellent, and the heat dissipation of the thermal conductor is excellent. The thermal conductivity of the thermally conductive material (II) can be measured by setting a sample in a sample holder for in-plane measurement by the laser flash method, and setting the size of the sample to a diameter of about 20 to 30 mm and a thickness of 1 mm or less. In addition, for materials that do not easily absorb laser light, a thin and uniform blackening film is formed on the surface of the sample. For materials with low emissivity at the temperature measurement wavelength of the infrared detection element, the same treatment is performed on the back side of the sample. In addition, in the present invention, the sheet-like refers to a thin and wide material, and means a material with a thickness of 0.01 μm to 10 mm and an aspect ratio of width to thickness of 10 or more.
[0028] The material of the thermally conductive material (II) is not particularly limited as long as it has an in-plane thermal conductivity of 300 W / m K or more. For example, ceramics, metals, graphite, and highly thermally conductive resins in which a highly thermally conductive filler has been added to the resin to increase the thermal conductivity can be used.
[0029] Furthermore, the thermally conductive material (II) preferably includes a thermally conductive sheet selected from the group consisting of a graphite sheet, a metal sheet, and a ceramic sheet, and more preferably is a thermally conductive sheet selected from the group consisting of a graphite sheet, a metal sheet, and a ceramic sheet. Examples of the ceramic sheet include sheets of silica, zirconia, alumina, boron nitride, silicon carbide, silicon nitride, etc. Examples of the metal sheet include sheets of titanium, aluminum, magnesium, iron, silver, gold, platinum, copper, nickel, or alloys mainly composed of these elements.
[0030] Metal sheets are relatively inexpensive, and among them, copper sheets are inexpensive and have excellent thermal conductivity, so they are preferable from the viewpoint of raw material costs.Graphite sheets have a small specific gravity and excellent thermal conductivity, so they are particularly preferable in the present invention from the viewpoint of improving the light weight and heat dissipation of the thermal conductor.
[0031] Examples of graphite sheets include sheets made by mixing graphite powder with a binder resin, or sheets made by rolling expanded graphite, sheets made by laminating carbon atoms on a substrate by a CVD method using a hydrocarbon gas and then annealing, sheets made by graphitizing a polymer film, etc. Among these, sheets made by graphitizing a polymer film are preferred because they have very high thermal conductivity.
[0032] In the present invention, the thermal conductive material (II) preferably includes a laminated structure of a plurality of thermal conductive sheets, and more preferably is a laminated structure of a plurality of thermal conductive sheets. In particular, the orientation of the graphene structure in the graphite sheet affects the thermal conductivity, and generally, a thinner graphite sheet has a higher thermal conductivity. Therefore, when a graphite sheet is used as the thermal conductive sheet, the heat dissipation of the thermal conductor can be improved by using a laminated structure of a plurality of sheets as the thermal conductive material (II). In this case, it is preferable that the plurality of thermal conductive sheets constituting the thermal conductive material (II) are in direct contact with each other without the intervention of an adhesive or the like. By directly contacting the thermal conductive sheets with each other, the proportion of the thermal conductive material (II) in the thermal conductor can be increased, and the heat dissipation of the thermal conductor is improved. In addition, by directly contacting the thermal conductive sheets with each other, the thermal diffusion in the out-of-plane direction is also excellent. The number of laminated sheets of the thermal conductive sheets is preferably 2 to 10, and more preferably 3 to 5. Increasing the number of laminated sheets improves the heat dissipation of the thermal conductor. On the other hand, if the number of layers is increased too much, the processability decreases.
[0033] The average thickness of the thermal conductive material (II) is preferably 0.01 μm or more and 2.0 mm or less, more preferably 5 μm or more and 1.0 mm or less, and even more preferably 15 μm or more and 0.5 mm or less. If the average thickness of the thermal conductive material (II) is too small, the heat dissipation of the thermal conductor will decrease, and if the average thickness of the thermal conductive material (II) is too large, the weight of the thermal conductor will be heavy. The method for measuring the average thickness of the thermal conductive material (II) is to measure the thickness of nine points of the thermal conductive material (II) to one decimal place using a micrometer, and the average value is the average thickness. The measurement points are measured at three points in each of the vertical and horizontal directions so that the intervals between each measurement point and the adjacent point or the sample end are equal in the vertical and horizontal directions, for a total of nine points.
[0034] [Porous structure (I)] The material of the porous structure (I) is not particularly limited as long as it is a fiber-reinforced resin composed of reinforcing fibers and resin. For example, it may be a continuous fiber impregnated with a resin containing a foaming agent and foamed, a discontinuous fiber impregnated with a resin containing a foaming agent and foamed, or a discontinuous fiber impregnated with a resin and expanded by the springback of the discontinuous fiber. The continuous reinforcing fiber means a reinforcing fiber that is continuous in at least one direction over a length of 15 mm or more, preferably 100 mm or more. Being a fiber-reinforced resin is advantageous in terms of the lightness and rigidity of the thermal conductor. In addition, when the thermal conductive material (II) is contained in the porous structure (I), the porous structure (I) is crushed or expanded in the out-of-plane direction, so that the thermal conductive material (II) is not displaced and the porous structure (I) can contain the thermal conductive material (II).
[0035] The volume content of voids in the porous structure (I) is preferably 10% or more and 85% or less, more preferably 20% or more and 85% or less, relative to the apparent volume of the porous structure (I), and even more preferably 50% or more and 80% or less, from the viewpoint of achieving both light weight and mechanical properties.
[0036] From the viewpoint of the light weight of the thermal conductor, the specific gravity of the porous structure (I) is preferably 0.01 to 1.5, more preferably 0.1 to 1.3, and further preferably 0.3 to 1.1. The specific gravity is measured by cutting out the porous structure (I) and measuring it in accordance with ISO0845 (1988).
[0037] There is no particular limit to the type of reinforcing fiber contained in the porous structure (I), and for example, carbon fiber, glass fiber, aramid fiber, alumina fiber, silicon carbide fiber, boron fiber, metal fiber, natural fiber, mineral fiber, etc. can be used, and these may be used in combination of one or more types. Among them, PAN-based, pitch-based, rayon-based carbon fibers are preferably used from the viewpoint of high specific strength and specific rigidity and weight reduction effect. In addition, glass fiber can be preferably used from the viewpoint of improving the economic efficiency of the obtained thermal conductor, and it is particularly preferable to use carbon fiber and glass fiber in combination from the viewpoint of balance between mechanical properties and economic efficiency. Furthermore, aramid fiber can be preferably used from the viewpoint of improving the impact absorption and formability of the obtained thermal conductor, and it is particularly preferable to use carbon fiber and aramid fiber in combination from the viewpoint of balance between mechanical properties and impact absorption. In addition, reinforcing fiber coated with metal such as nickel, copper, or ytterbium, or pitch-based carbon fiber can be used from the viewpoint of improving the conductivity of the obtained thermal conductor.
[0038] From the viewpoint of improving mechanical properties, it is preferable that the reinforcing fiber is surface-treated with a sizing agent. Examples of the sizing agent include polyfunctional epoxy resins, acrylic acid-based polymers, polyhydric alcohols, and polyethyleneimines. Specifically, polyglycidyl ethers of aliphatic polyhydric alcohols such as glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitol polyglycidyl ether, arabitol polyglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol polyglycidyl ether, polyacrylic acid, copolymers of acrylic acid and methacrylic acid, acrylic acid, and acrylic acid are preferably used. Examples of suitable epoxy resins include copolymers of glyceryl and maleic acid, or mixtures of two or more of these, polyvinyl alcohol, glycerol, diglycerol, polyglycerol, sorbitol, arabitol, trimethylolpropane, pentaerythritol, and polyethyleneimine containing a large number of amino groups per molecule. Among these, glycerol triglycidyl ether, diglycerol polyglycidyl ether, and polyglycerol polyglycidyl ether are preferably used because they contain a large number of highly reactive epoxy groups per molecule, are highly water-soluble, and are easy to apply.
[0039] The resin contained in the porous structure (I) is not particularly limited, and may be a thermosetting resin or a thermoplastic resin. Examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyethylene naphthalate (PEN), and liquid crystal polyesters, polyolefins such as polyethylene (PE), polypropylene (PP), and polybutylene, polyarylene sulfides such as polyoxymethylene (POM), polyamide (PA), and polyphenylene sulfide (PPS), and fluorine-based resins such as polyketone (PK), polyether ketone (PEK), polyether ether ketone (PEEK), polyether ketone ketone (PEKK), polyether nitrile (PEN), and polytetrafluoroethylene. Examples of the thermoplastic resin include crystalline resins, amorphous resins such as "styrene-based resins, polycarbonate (PC), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyphenylene ether (PPE), polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polysulfone (PSU), polyethersulfone, and polyarylate (PAR)" and other phenolic resins, phenoxy resins, and thermoplastic elastomers such as polystyrene, polyolefin, polyurethane, polyester, polyamide, polybutadiene, polyisoprene, fluorine-based resins, and acrylonitrile, as well as copolymers and modified products thereof. Among these, polyolefins are preferred from the viewpoint of the lightness of the resulting thermal conductor. Polyamides are also preferred from the viewpoint of strength. In particular, when the porous structure (I) is made of fiber-reinforced resin, polyamides are preferred from the viewpoint of the interfacial bonding strength between the reinforcing fibers and the resin. Examples of the thermosetting resin include unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol (resol) resin, urea resin, melamine resin, polyimide resin, maleimide resin, benzoxazine resin, and a blend of two or more of these. Among these, when the porous structure (I) is made of a fiber-reinforced resin, an epoxy resin is preferably used from the viewpoint of the interfacial bonding strength between the reinforcing fiber and the resin.
[0040] Furthermore, the resin may contain, depending on its application, fillers such as mica, talc, kaolin, hydrotalcite, sericite, bentonite, xonotlite, sepiolite, smectite, montmorillonite, wollastonite, silica, calcium carbonate, glass beads, glass flakes, glass microballoons, clay, molybdenum disulfide, titanium oxide, zinc oxide, antimony oxide, calcium polyphosphate, graphite, barium sulfate, magnesium sulfate, zinc borate, calcium borate, aluminum borate whisker, potassium titanate whisker, and polymer compounds; conductive materials such as metals, metal oxides, carbon black, and graphite powder; halogen-based flame retardants such as brominated resins, antimony-based flame retardants such as antimony trioxide and antimony pentoxide, phosphorus-based flame retardants such as ammonium polyphosphate, aromatic phosphate, and red phosphorus; and other additives such as metal borates, metal carboxylates, and aromatic sulfonimide metal salts. Organic acid metal salt flame retardants, inorganic flame retardants such as zinc borate, zinc, zinc oxide and zirconium compounds, nitrogen-based flame retardants such as cyanuric acid, isocyanuric acid, melamine, melamine cyanurate, melamine phosphate and nitrogenated guanidine, fluorine-based flame retardants such as PTFE, silicone-based flame retardants such as polyorganosiloxane, metal hydroxide-based flame retardants such as aluminum hydroxide and magnesium hydroxide, and other flame retardants, cadmium oxide, zinc oxide, cuprous oxide Flame retardant assistants such as cupric oxide, ferrous oxide, ferric oxide, cobalt oxide, manganese oxide, molybdenum oxide, tin oxide and titanium oxide, pigments, dyes, lubricants, release agents, compatibilizers, dispersants, crystal nucleating agents such as mica, talc and kaolin, plasticizers such as phosphate esters, heat stabilizers, antioxidants, coloring inhibitors, ultraviolet absorbers, flow modifiers, foaming agents, antibacterial agents, vibration dampers, deodorants, sliding modifiers, and antistatic agents such as polyether ester amides may also be added. In particular, when the application is for electrical and electronic equipment, automobiles, aircraft, etc., flame retardancy may be required, and phosphorus-based flame retardants, nitrogen-based flame retardants and inorganic flame retardants are preferably added. In order to maintain a good balance between the mechanical properties of the resin used and the resin fluidity during molding while exhibiting a flame retardant effect, the amount of the flame retardant is preferably 1 to 20 parts by mass, more preferably 1 to 15 parts by mass, per 100 parts by mass of the resin.
[0041] In the thermal conductor of the present invention, it is particularly preferable that the porous structure (I) is made of a discontinuous fiber reinforced resin. The discontinuous fiber reinforced resin has a structure in which discontinuous fibers form a three-dimensional network and the intersections of the discontinuous fibers are bonded by a resin. By bonding the discontinuous fibers by a resin, the shear modulus of the porous structure (I) is increased, and the rigidity of the thermal conductor is increased. This embodiment will be described below.
[0042] In the discontinuous fiber reinforced resin, the discontinuous fibers are preferably present as fine strands of less than 500 fibers, and more preferably present dispersed as single fibers. The fiber length of the discontinuous fibers is preferably 1 to 50 mm, and more preferably 3 to 30 mm. If the fiber length is 1 mm or more, the reinforcing effect of the discontinuous fibers can be efficiently exhibited. Also, if the fiber length is 50 mm or less, the dispersion of the discontinuous fibers can be maintained well.
[0043] The ratio of the number of bonded portions where single filaments of the discontinuous fibers are bonded to each other by a resin to the total number of crossing portions where the discontinuous fibers cross each other is 50% or more, more preferably 70% or more, and even more preferably 90% or more.
[0044] From the viewpoint of achieving both mechanical properties and moldability, the mass proportion of the discontinuous fibers in the porous structure (I) is preferably 5 to 60 mass %, more preferably 10 to 50 mass %, and further preferably 15 to 40 mass %.
[0045] In the porous discontinuous fiber reinforced resin, it is preferable that 30% or more, more preferably 50% or more, and even more preferably 80% or more of the surface of the discontinuous fiber is covered with the resin. By achieving such a coverage, the rigidity of the porous structure (I) can be increased. The coverage is measured by observing the cross section of the porous structure (I) with a scanning electron microscope (SEM) to distinguish the reinforcing fiber from the resin.
[0046] The pores of the porous discontinuous fiber reinforced resin preferably have an average pore diameter of 200 μm or less as measured by mercury intrusion porosimetry. The average pore diameter is preferably 10 μm or more and 150 μm or less, and more preferably 30 μm or more and 100 μm or less. If the average pore diameter is smaller than this range, the weight reduction and hardening may not be sufficient, and if the average pore diameter is larger than this range, the mechanical properties may deteriorate. Mercury intrusion porosimetry is a method for measuring pore diameter using a mercury intrusion porosimeter, in which mercury is injected into a sample at high pressure, and the pore diameter can be obtained from the applied pressure and the amount of mercury injected. The average pore diameter can be calculated by the following formula. ·Average pore diameter (m) = 4 x pore volume (m 3 / g) / specific surface area (m 2 / g) <Method of manufacturing thermal conductor> The method for producing a thermal conductor of the present invention is a method for producing a thermal conductor of the present invention, and includes the steps of arranging a precursor of a porous structure (I) on at least one surface and at least one end face of the thermal conductive material (II) and hot pressing, in this order. By using such a method, molding and bonding of the porous structure (I) can be performed simultaneously, resulting in excellent productivity. In the method for producing a thermal conductor of the present invention, "arranging a precursor of a porous structure (I) on at least one surface and at least one end face of the thermal conductive material (II)" means arranging the precursor of the porous structure (I) so as to cover at least one surface and at least one end face of the thermal conductive material (II).
[0047] In the method for producing a thermal conductor of the present invention, it is preferable that the precursor of the porous structure (I) is disposed on both sides of the thermal conductive material (II). In the method for producing a thermal conductor of the present invention, it is more preferable that the precursor of the porous structure (I) is disposed on at least two end faces of the thermal conductive material (II), more preferably on both sides of the thermal conductive material (II), and it is particularly preferable that the precursor is disposed on both sides and all end faces of the thermal conductive material (II), that is, the precursor contains the thermal conductive material (II).
[0048] When the porous structure (I) is composed of a discontinuous fiber reinforced resin, the precursor of the porous structure (I) can be produced by compressing and impregnating a thermoplastic resin film or nonwoven fabric into a discontinuous reinforcing fiber mat. The discontinuous reinforcing fiber mat is produced, for example, by dispersing discontinuous reinforcing fibers in advance in a strand shape, preferably in a substantially monofilament shape, more preferably in a monofilament shape. More specifically, known techniques include an airlaid method in which discontinuous reinforcing fibers are dispersed in an air flow to form a sheet, a dry process such as a carding method in which discontinuous reinforcing fibers are mechanically scraped into a sheet, and a wet process by the Radlite method in which discontinuous reinforcing fibers are stirred in water and paper is made.
[0049] Examples of means for making the discontinuous reinforcing fibers closer to single fibers in the dry process include a means for providing a fiber opening bar, a means for vibrating the fiber opening bar, a means for making the card finer, and a means for adjusting the rotation speed of the card. Examples of means for making the discontinuous reinforcing fibers closer to single fibers in the dry process include a means for adjusting the stirring conditions of the discontinuous reinforcing fibers, a means for diluting the reinforcing fiber concentration of the dispersion, a means for adjusting the viscosity of the dispersion, and a means for suppressing vortexes when transferring the dispersion. In particular, the discontinuous reinforcing fiber mat is preferably produced by a wet method, and the proportion of reinforcing fibers in the discontinuous reinforcing fiber mat can be easily adjusted by increasing the concentration of the input fibers or adjusting the flow rate (flow rate) of the dispersion and the speed of the mesh conveyor. For example, by slowing down the speed of the mesh conveyor relative to the flow rate of the dispersion, the orientation of the fibers in the obtained discontinuous reinforcing fiber mat is less likely to face the take-up direction, and a bulky discontinuous reinforcing fiber mat can be produced. The discontinuous reinforcing fiber mat may be composed of discontinuous reinforcing fibers alone, or the discontinuous reinforcing fibers may be mixed with a powder-shaped or fibrous matrix resin component, the discontinuous reinforcing fibers may be mixed with an organic or inorganic compound, or the discontinuous reinforcing fibers may be sealed together with a resin component.
[0050] The pressure when the thermoplastic resin film or nonwoven fabric is impregnated into the discontinuous reinforcing fiber mat is preferably 0.5 MPa or more and 30 MPa or less, more preferably 1 MPa or more and 5 MPa or less. If the pressure is less than 0.5 MPa, the thermoplastic resin may not be impregnated into the discontinuous reinforcing fiber mat, and if it is greater than 30 MPa, it becomes difficult to adjust the thickness of the precursor of the porous structure. The temperature when the thermoplastic resin film or nonwoven fabric is impregnated is preferably a temperature equal to or higher than the melting point or glass transition point of the thermoplastic resin, more preferably a temperature equal to or higher than the melting point or glass transition point plus 10 ° C., and even more preferably a temperature equal to or higher than the melting point or glass transition point plus 20 ° C. If the temperature when the thermoplastic resin film or nonwoven fabric is impregnated is too high, decomposition or deterioration of the thermoplastic resin may occur, so it is preferably equal to or lower than the melting point or glass transition point of the thermoplastic resin plus 150 ° C.
[0051] As equipment for realizing the method of impregnating a discontinuous reinforcing fiber mat with a thermoplastic resin film or nonwoven fabric, a compression molding machine or a double belt press machine can be suitably used. The compression molding machine is a batch type, and productivity can be improved by forming an intermittent press system in which two or more machines for heating and cooling are arranged in parallel. The double belt press machine is a continuous type, and is excellent in continuous productivity because continuous processing can be easily performed.
[0052] The method for producing a thermal conductor of the present invention includes a step of hot pressing. In this step, a precursor of the porous structure (I) is placed on at least one surface and at least one end surface of the thermal conductive material (II), and the thermal conductive material can be impregnated into the core material by hot pressing at the expansion temperature of the precursor of the porous structure (I) or a temperature required for bonding. In this case, when a discontinuous reinforcing fiber mat is used, the resin impregnated in the discontinuous reinforcing fiber mat melts or softens to release the compressed state, causing springback. This springback forms fine voids to form a porous discontinuous fiber reinforced resin. A compression molding machine can be suitably used as the equipment for the hot pressing. The compression molding machine is a batch type, and productivity can be improved by forming an intermittent press system in which two or more machines for heating and cooling are arranged in parallel.
[0053] <Case> The housing of the present invention is made using the thermal conductor of the present invention. By using the thermal conductor of the present invention, a housing having both excellent mechanical properties and light weight can be obtained. In addition, from the viewpoint of mass production, it is preferable because it can be molded by high-cycle molding such as press molding.
[0054] The housing of the present invention can be obtained, for example, by producing a thermal conductor having a desired shape for the housing by the above-mentioned method for producing a thermal conductor. EXAMPLES
[0055] The present invention will now be described in more detail with reference to examples.
[0056] (1) Measurement of bending modulus of thermal conductor The bending properties of the prepared thermal conductor bending test pieces were measured according to ISO178 (1993). The number of measurements was 5 (n=5), and the average value was taken as the bending modulus. The measurement device used was an Instron Japan Co., Ltd. "Instron" (registered trademark) 5565 type universal material testing machine.
[0057] (2) Heat dissipation evaluation of thermal conductors As shown in Figure 4, rubber spacers 5 measuring 10 mm x 10 mm and 3 mm thick were attached to the four corners of the back surface of the prepared thermal conductor 1, and the thermal conductor was placed on a laboratory bench. A micro ceramic heater 4 measuring 50 mm x 25 mm (Micro Ceramic Heater MS-2 (product name) manufactured by Sakaguchi Electric Heater Co., Ltd.) was placed on one corner of the front surface of the placed thermal conductor, and the heater was heated at 10 W under constant current and constant voltage. The heat dissipation performance was evaluated based on the heater temperature when it became constant 15 minutes after the start of heating, according to the following criteria. A: Heater temperature below 130℃ (high heat dissipation) B: Heater temperature 130℃ or higher (low heat dissipation) (Reference Example 1) Preparation of carbon fiber bundles A polymer mainly composed of polyacrylonitrile was spun and baked to obtain a continuous carbon fiber bundle with a total of 12,000 filaments. A sizing agent was applied to the continuous carbon fiber bundle by a dipping method, and the bundle was dried in air at 120°C to obtain a carbon fiber bundle. The properties of this carbon fiber bundle were as follows.
[0058] Single fiber diameter: 7μm Mass per unit length: 0.8g / m Density: 1.8g / cm 3 Tensile strength: 4.2GPa Tensile modulus: 230GPa Sizing type: Polyoxyethylene oleyl ether Sizing adhesion amount: 1.5% by mass (Reference Example 2) Preparation of carbon fiber mat The carbon fiber bundle of Reference Example 1 was cut to a fiber length of 6 mm with a cartridge cutter to obtain a chopped carbon fiber bundle. An aqueous dispersion of 0.1 mass % of a surfactant (Polyoxyethylene lauryl ether (product name) manufactured by Nacalai Tesques, Inc.) was prepared, and the dispersion and the chopped carbon fiber bundle were put into a papermaking machine to produce a carbon fiber mat.
[0059] The papermaking machine is equipped with a dispersion tank, a papermaking tank, and a transport section connecting the dispersion tank and the papermaking tank. The dispersion tank is equipped with an agitator and can disperse the dispersion liquid and chopped carbon fiber bundles that have been put in. The papermaking tank is equipped with a mesh conveyor having a papermaking surface at the bottom, and a conveyor capable of transporting the paper-made carbon fiber mat is connected to the mesh conveyor. The papermaking was performed with a fiber concentration in the dispersion liquid of 0.05% by mass. The paper-made carbon fiber mat was dried in a drying oven at 200°C. Then, a 3% by mass aqueous dispersion of a binder (manufactured by Nippon Shokubai Co., Ltd., "Polyment" (registered trademark) SK-1000) was sprayed as a binder on the upper surface of the carbon mat transported by the conveyor. The excess binder was sucked and dried in a drying oven at 200°C to obtain a carbon fiber mat. The basis weight of the obtained carbon fiber mat was 50 g / m 2 It was.
[0060] (Reference Example 3) Preparation of polypropylene resin film 90% by mass of unmodified polypropylene resin (Prime Polymer Co., Ltd., "Prime Polypro" (registered trademark) J105G) was blended with 10% by mass of acid-modified polypropylene resin (Mitsui Chemicals, Inc., "Admer" (registered trademark) QE510). This blend was melt-kneaded in an extruder and then extruded from a T-shaped die. Thereafter, the resin was taken up on a chill roll at 60°C and cooled and solidified to obtain a polypropylene resin film.
[0061] Example 1 A thermal conductor was produced using the carbon fiber mat of Reference Example 2, the polypropylene resin film of Reference Example 3, and a graphite sheet (manufactured by Panasonic Corporation, "PGS" (registered trademark) EYGS182307, in-plane thermal conductivity 1000 W / m·K). The carbon fiber mat and the polypropylene resin film were adjusted to a size of 50 mm × 150 mm, and the graphite sheet was adjusted to a size of 40 mm × 140 mm, and then laminated in the following order: [polypropylene resin film / carbon fiber mat / polypropylene resin film / carbon fiber mat / graphite sheet / carbon fiber mat / polypropylene resin film / carbon fiber mat / polypropylene resin film]. At this time, the graphite sheet was placed in the center of the laminate. This laminate was sandwiched between release films and further sandwiched between tool plates. They were placed in a press molding machine with a plate surface temperature of 180 ° C., and heat pressed at 3 MPa for 10 minutes, thereby impregnating the carbon fiber mat with polypropylene resin. Next, a spacer having a thickness of 1 mm was inserted between the tool plates, and the plate surface temperature was 40°C. The laminate was cooled and pressed at a surface pressure of 3 MPa until it cooled, thereby obtaining a thermal conductor in which a porous structure was arranged around the thermal conductive material. The thickness of the sample was measured with a micrometer, and the thickness was 1.0 mm. By inserting a spacer having a thickness of 1 mm between the tool plates, the carbon fiber mat impregnated with polypropylene resin springs back and becomes a porous structure. In addition, since the sample in this embodiment is a flat plate, the thickness is constant. Therefore, the thickness measured at any point of the sample is the maximum thickness. The same applies to other examples and comparative examples. In addition, the bending test piece was preformed and press molded in the same manner, except that the carbon fiber mat and the polypropylene resin film were adjusted to a size of 50 mm x 40 mm, and the graphite sheet was adjusted to a size of 40 mm x 30 mm, and a bending test piece of a thermal conductor in which a porous structure was arranged around the thermal conductive material was obtained. The obtained thermal conductor exhibited excellent rigidity, light weight, and heat dissipation properties because the graphite sheet was protected by a porous structure containing reinforcing fibers.
[0062] Example 2 Except for changing the number of polypropylene resin films and carbon fiber mats and laminating them in the order of [polypropylene resin film / carbon fiber mat / graphite sheet / carbon fiber mat / polypropylene resin film / carbon fiber mat / polypropylene resin film], preforming and press molding were performed in the same manner as in Example 1 to obtain a thermal conductor in which a porous structure was arranged around the thermal conductive material, and a bending test piece of the thermal conductor. The obtained thermal conductor showed superior lightness due to an increased porosity while maintaining excellent rigidity and heat dissipation properties.
[0063] Comparative Example 1 The number of polypropylene resin films was adjusted so that the thickness of the laminate was 1.0 mm without laminating the carbon fiber mat, and the polypropylene resin film and the graphite sheet were laminated in the order of [polypropylene resin film / graphite sheet / polypropylene resin film]. Preforming and press molding were performed in the same manner as in Example 1, except that the polypropylene resin was arranged around the thermal conductive material, and a bending test piece of the thermal conductor was obtained. The obtained thermal conductor was inferior in lightness because the graphite sheet was protected by dense resin without voids. In addition, since it did not contain reinforcing fibers, its rigidity was also low.
[0064] Comparative Example 2 A graphite sheet and a foamed polypropylene sheet (manufactured by Furukawa Electric Industry Co., Ltd., "F-Cell" (registered trademark) RC2008W, density 0.46 g / cm 3 ) was used, the thickness of the foamed polypropylene sheet was adjusted to 0.5 mm, and the layers were laminated in the order of [foamed polypropylene sheet / graphite sheet / foamed polypropylene sheet]. Except for this, preforming and press molding were performed in the same manner as in Example 1 to obtain a thermal conductor in which foamed polypropylene was arranged around the thermal conductive material. The obtained thermal conductor was protected by the foamed resin and therefore exhibited excellent lightness, but had extremely low rigidity.
[0065] Comparative Example 3 Preforming and press molding were performed in the same manner as in Example 1, except that the graphite sheet was not laminated, to obtain a thermal conductor not containing a thermal conductive material. Similarly, when preparing a bending test piece, preforming and press molding were performed in the same manner as in Example 1, except that the graphite sheet was not laminated, to obtain a bending test piece of a thermal conductor not containing a thermal conductive material. The obtained thermal conductor did not contain a thermal conductive material, so that the heat dissipation was low.
[0066] Comparative Example 4 Preforming and press molding were performed in the same manner as in Example 1, except that the size of the graphite sheet was adjusted to a size of 50 x 150 mm, to obtain a thermal conductor in which all ends of the thermal conductive material were exposed. In addition, when preparing a bending test piece, preforming and press molding were performed in the same manner as in Example 1, except that the size of the graphite sheet was adjusted to a size of 50 mm x 40 mm, to obtain a bending test piece of a thermal conductor in which all ends of the thermal conductive material were exposed. In the obtained thermal conductor, since all ends of the graphite sheet were exposed, peeling occurred between the layers of the graphite sheet, and the rigidity was reduced.
[0067] [Table 1] [Industrial Applicability]
[0068] The thermal conductor of the present invention can achieve both excellent lightness and excellent rigidity. Therefore, it can be applied to a wide range of industrial fields as a structural member of electric / electronic devices, robots, motorcycles, automobiles, aircraft, etc. In particular, it can be preferably applied to the housing of portable electronic devices and the like that require high lightness. [Explanation of symbols]
[0069] 1. Thermal Conductors 2. Porous structure (I) 3. Thermal Conductive Materials (II) 4. Heater 5. Rubber spacers
Claims
1. A thermal conductor comprising a porous structure (I) composed of reinforcing fibers and a resin, and a sheet-like thermal conductive material (II) having an in-plane thermal conductivity of 300 W / m·K or more contained therein.
2. The thermal conductor according to claim 1 , wherein the porous structure (I) covers at least one surface and at least one end face of the thermal conductive material (II).
3. The thermal conductor according to claim 2 , wherein the porous structure (I) covers both sides and all end faces of the thermal conductive material (II).
4. The thermal conductor according to any one of claims 1 to 3, wherein the thermally conductive material (II) comprises a thermally conductive sheet selected from the group consisting of a graphite sheet, a metal sheet, and a ceramic sheet.
5. The thermal conductor according to claim 4 , wherein the thermally conductive material (II) comprises a laminated structure of a plurality of the thermally conductive sheets.
6. The thermal conductor according to any one of claims 1 to 5, wherein the porous structure (I) is made of discontinuous fiber reinforced resin.
7. The thermal conductor according to any one of claims 1 to 6, having a flexural modulus of 3 GPa or more.
8. The thermal conductor according to any one of claims 1 to 7, having a bending stiffness per unit width of 0.3 N·m or more.
9. The thermal barrier according to any one of claims 1 to 8, wherein the maximum thickness is 0.3 mm or more and 3.0 mm or less. Conductor.
10. The thermal conductor according to any one of claims 1 to 9, having a specific gravity of 1.00 or less.
11. A housing comprising the thermal conductor according to any one of claims 1 to 10.
12. A method for producing the thermal conductor according to any one of claims 1 to 10, comprising the steps of arranging a precursor of a porous structure (I) on at least one surface and at least one end surface of the thermal conductive material (II) and hot pressing the precursor, in this order.
Citation Information
Patent Citations
Thermally conductive sheet
JP2002038033A
High thermal conductive frame and graphite prepreg
JP2006095935A
Heat diffusion sheet
JP2010010599A
Graphite composite film
JP2010064391A
Composite sheet and production method of the same, and electronic equipment using composite sheet
JP2016028880A